2006
DOI: 10.1002/sim.2760
|View full text |Cite
|
Sign up to set email alerts
|

On the exact interval estimation for the difference in paired areas under the ROC curves

Abstract: An important measure for comparison of accuracy between two diagnostic procedures is the difference in paired areas under the receiver operating characteristic (ROC) curves. Non-parametric and maximum likelihood methods have been proposed for interval estimation for the difference in paired areas under ROC curves. However, these two methods are asymptotic procedures and their performance in finite sample sizes has not been thoroughly investigated. We propose to use the concept of generalized pivotal quantities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 32 publications
(32 reference statements)
0
33
0
Order By: Relevance
“…The concepts of generalized confidence interval and generalized p -value have been successfully applied to a variety of practical settings where standard exact solutions do not exist for confidence intervals and hypothesis testing. It has been shown that generalized inference approaches generally have good performance, even at small sample sizes (see e.g., Weerahandi, 1995; Weerahandi and Berger, 1999; Krishnamoorthy and Lu, 2003; Tian and Cappelleri, 2004; Tian, 2008; Li et al, 2008a, 2008b). …”
Section: Parametric Approachesmentioning
confidence: 99%
“…The concepts of generalized confidence interval and generalized p -value have been successfully applied to a variety of practical settings where standard exact solutions do not exist for confidence intervals and hypothesis testing. It has been shown that generalized inference approaches generally have good performance, even at small sample sizes (see e.g., Weerahandi, 1995; Weerahandi and Berger, 1999; Krishnamoorthy and Lu, 2003; Tian and Cappelleri, 2004; Tian, 2008; Li et al, 2008a, 2008b). …”
Section: Parametric Approachesmentioning
confidence: 99%
“…Tsui and Weerahandi [5], and Weerahandi [6] propose the generalized confidence interval (GCI) based on the generalized pivotal quantity (GPQ) for the exact statistical inference. It has been successfully applied to various areas including population and individual bioequivalence [7], tolerance intervals for quality control [8,9], and the area under the receiver operating characteristic (ROC) curve [10,11]. As a result, we propose to apply the concept of GCI for validation of quantitative analytical laboratory procedures.…”
Section: Introductionmentioning
confidence: 98%
“…While the conventional frequentist methods fail to provide satisfactory solutions for interval estimation because of complex parametric functions situations, GPQs can serve as tractable means of providing GCIs. The GCIs have been applied successfully to many biological studies such as occupational exposure limit [9,10]; population and individual bioequivalence, [16]; accuracy comparison with receiver operating characteristic curves [13]; tolerance intervals for random effects models [14]; etc. The simulation studies presented in the aforementioned literatures strongly support that the coverage probabilities of GCI approach perform well especially in small sample sizes.…”
Section: Introductionmentioning
confidence: 99%